2021
DOI: 10.1080/2162402x.2021.1929725
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for an old target: CD45 for breast cancer immunotherapy

Abstract: Breast cancer subtypes have not shown significant response to current immunomodulatory therapies. Although most subtypes are treatable, triple negative breast cancer (TNBC), an aggressive highly metastatic cancer, comprising 10–20% of breast cancers, remains an unmet medical need. New strategies are needed in order to overcome flaws in the responsiveness to current TNBC therapies. Our aims were: first, to determine the efficacy of a novel immunomodulatory peptide, C24D, on TNBC and second, to elucidate the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
1
9
1
Order By: Relevance
“…Similar to our findings on TNBC tumors ( 8 ), viral interference with the functions of the receptor tyrosine phosphatase CD45 have been widely reported. It was demonstrated that CD45 functions are crucial for stimulating a protective immune response against Herpes simplex virus type 1 (HSV-1) ( 29 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our findings on TNBC tumors ( 8 ), viral interference with the functions of the receptor tyrosine phosphatase CD45 have been widely reported. It was demonstrated that CD45 functions are crucial for stimulating a protective immune response against Herpes simplex virus type 1 (HSV-1) ( 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…We recently reported an immune escape mechanism in TNBC patients showing that CD45's intracellular signals are inhibited ( 8 ). We also reported that C24D, a previously described immune modulating therapeutic peptide ( 9 ), binds to the CD45 receptor of the TNBC-suppressed immune cells and reverses immune-suppression, via the CD45 signaling pathway ( 8 ). C24D-binding to CD45 in the immune-suppressed cells resulted in immune reactivation and specific tumor killing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that CD45 is the receptor of CD24D, and the immunomodulatory peptide CD24D can reverse the immunosuppression induced by TNBC by activating the CD45 signaling pathway, and participate in the biological process of immunomodulatory tumor cell killing. CD45 may be the target of TNBC immune response recovery ( Raiter et al, 2021 ). In conclusion, we believe that even though these five hub genes are not all expressed on macrophages, they can all play a role through macrophages, which also demonstrates the accuracy of them as macrophage-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…The former is associated with immune disorders including autoimmune hepatitis, HIV infection, and multiple sclerosis, while A138G is associated with hepatitis B, Graves´ disease, and severe combined immunodeficiency [ 16 , 17 , 18 ]. Furthermore, CD45 has been shown to be involved in tumor-induced immunosuppression in peripheral blood mononuclear cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an initial experiment, we demonstrated that LPS increases CD45 expression of granulocytes, lymphocytes, and monocytes. We therefore decided to study: (1) the ex vivo effect of LPS in volunteers, (2) the CD45 expression in an inflammatory disease (COVID- 19), and (3) the eventual differences in LPS-induced CD45 expression in volunteers and COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%